An Empirical Study of Growth Prospects of Micro, Small and Medium Enterprises in the Development of Uttarakhand - Sonia; Yadav, Arvind Kumar (Journal of Commerce and Trade, 2019)
Micro, small and medium enterprises (MSMEs) in India and abroad have demonstrated considerable strength and resilience in maintaining a consistent rate of growth and employment generation during the global recession and economic slowdown. MSME is second largest employment provider after agriculture sector in India. It provides 80 % of jobs in the industry with just 20% of the investment. They also check rural urban migration by providing people living in isolated area with a sustainable source of employment. In India it contributes about 31% to the nation's GDP, 45% share in overall exports and 34% share in the manufacturing output as per 2017 reports.For all developing countries like India where poverty, unemployment and underemployment are the major problem of millions of people, the Micro, Small & Medium enterprises (MSMEs) has often been act as a growth engine by providing immediate largescale employment, with lower investments. More than 65 million micro, small, and medium enterprises (MSMEs) in the country form the backbone of the economy. The segment is in dire need of relief packages, support in working capital loans, and strengthening or fixing of supply chains which have been disrupted, among other needs. The Uttarakhand government has generated its MSME policy, which means to support enterprise, end outward movement and realize comprehensive advancement in the state, particularly in the remote and flood-hit hill zones. The MSME policy of Uttarakhand offers a few incentives like interest subsidy and VAT reimbursement, capital investment subsidy. Classification-JEL : L52, O14